Applying strategic planning to an SME : a case study on United Bakery Supplies Pte Ltd. - Neu, Boon Ling. (2008)
SMEs are always characterised by the central position of the owner, who sometimes has limited managerial qualification and significant aversion against planning and the application of formal methods. That, coupled with the limitations that SMEs face, such as limited resources, lack of specialist expertise and limited impact in the marketplace, means that conventional strategic management approaches may not always work for them. In this project, we applied various strategic management frameworks to the context of an SME to determine if its operations can be improved by higher level of strategic planning. A case study analytical approach had been adopted and our study focused on United Bakery Supplies Pte Ltd (UBS), an established bakery supplies distributor in Singapore which had agreed to let us perform a management consultancy project for them. We began by reviewing background information. Then, we analysed this information using various frameworks. Following that, we formulated strategic decisions and propose recommendations to UBS’s management. Lastly, we implemented those recommendations that were within our abilities to do so and measured their effectiveness. In this way, theoretical frameworks were put to test in a real and dynamic context and their usefulness on SMEs understood.